Factors Influencing the Intention of Using Gopay by the Millennial Generation in Medan City: Extended Technology Acceptance Model Approach - Rahma Fahmadina Lubis; Aqwa Naser Daulay; Siti Aisyah (Journal of Social Commerce, 2026)
The purpose of the study is to gain an in-depth understanding of how the Factors Affecting the Intention of Using Gopay by the Millennial Generation in Medan City: The Extended Technology Acceptance Model (TAM) Approach. The method used in this study is a quantitative approach with the IBM SPSS 26 tool. The population studied was the millennial generation who used digital payments, with 400 respondents through the purposive stratified sampling method, namely the sample extraction technique in the study where the researcher deliberately chose participants who had specific characteristics or criteria that were relevant to the research objectives. The results of the study show that perceived ease of use, perceived usefulness, perceived trust, perceived security, social influence and life competency have a significant effect on the intention of use.